Development and Validation of The Menstrual Health Outcome Questionnaire to evaluate quality of life among women during menstrual cycle (International Journal of Pharmaceutical Sciences and Drug Research, 2023)
Menstruation is a physiological process experienced by adolescent girls and women. Menstruation and premenstrual symptoms affect the Quality of Life. Different scales are available to measure QOL for different gynaecological problems but none scale available to measure QOL during Menstruation. WHO defines Quality of Life as an individual's perception of their position in life in the context of the culture and value systems in which they live and in relation to their goals, expectations, standards and concerns. It is a multidimensional concept that includes domains related to physical, mental, emotional and social functioning. It goes beyond direct measure of population health, life expectancy and causes of death and focuses on the impact health status on quality of life. To develop a comprehensive instrument to assess the health-related QOL among the women during menstruation. The creation of a scale to assess QOL during the menstrual cycle is indeed a significant endeavour. Menstrual Health Outcomes Questionnaire contains 35 questions from different domains. After getting ethical approval pilot and pivotal study conducted. Adolescents were randomly recruited in the study. Data was captured and entered in SPSS version 20. Principle factor analysis was determined to find construct validity among independent and dependent variables. Man-Whitney U test was determined. Questionnaire has Cronbach’s alpha 0.796, determined 35 questions. Intraclass corelation coefficient was found 0.786. KMO and Bartlett’s test was found 0.820 with high significance. (p=0.000) Menstrual Health Outcome Questionnaire has been established as a valid and reliable tool for assessing the QOL among women during menstruation.